Revisiting ECB’s Technocratic Legitimacy: No Longer Fit‐for‐Purpose? - Dimitrios Argyroulis; Nikolas Vagdoutis (Politics and Governance)
This article revisits the technocratic model of legitimacy that the European Central Bank (ECB) has enjoyed since its early period, by exploring the Monetary Policy Strategy statements that constitute the “comprehensive framework” guiding the Bank’s operational decisions. We examine whether the operational framework and the interpretation of the ECB’s legal mandate, which are included in these statements, are aligned with this model. We find that the ECB’s early monetary policy statements (1998 and 2003) appear to be aligned with this model, due to the presence of strictly defined performance criteria and an interpretation of the ECB’s mandate that was limited to pursuing price stability as a single objective. Our analysis of the ECB’s 2021 monetary policy strategy highlights its incompatibility with the technocratic model as a result of significant changes that enabled wide policy discretion and a re-interpretation of the ECB’s mandate, which revealed a largely vague and broad mandate. We argue that the ECB’s model of technocratic legitimacy is untenable in a democratic polity, given the extent and type of choices that the Governing Council is required to make in the current policy setting. Finally, we suggest that only a strengthening of the (hitherto diminished) input dimension of the ECB’s legitimacy could address this legitimacy gap.